Suspension of the procedure for the elimination of bureaucratic barriers when legal proceedings are in progress: Regarding the questioning of the prohibition on the use of labor outsourcing for the activities that comprise the “core business”. - Maraví Sumar, Milagros; Llacza Romero, Sheyla (Revista de Derecho, 2024)
The authors analyze the suspension of the procedure for the elimination of bureaucratic barriers when a judicial process is pending, taking as a reference the administrative procedure through which the prohibition of using outsourcing for activities that make up the "core business" is questioned. In this regard, they explain the reasons why it is considered that the mere existence of a pending judicial process should not justify the suspension of the administrative procedure, provided that the administrative authority has elements that allow it to prove that, regardless of what is resolved in judicial proceeding, an illegal and/or unreasonable bureaucratic barrier has been established that must be disapplied in favor of citizens and economic agents in the country.